KOGNITIV LINGVISTIKA HÁM LINGVOKULTUROLOGIYADA REŃ KONCEPTIN INGLIS TILI MATERIALLARÍ TIYKARÍNDA TALQÍLAW - Utepbergenova, Damegul Najimatdinovna (SCIENCE and SOCIETY, 2026)
This article explores the concept of color in the English language from cognitive and cultural perspectives. It shows that colors express not only physical features, but also emotions, ideas, and cultural meanings. English expressions like to feel blue, a white lie, black market, and green with envy demonstrate the metaphorical use of colors. The study explains that white symbolizes purity, black sadness, red danger, blue calmness, and green nature and growth. Color terms are widely used in literature, phraseology, advertising, and everyday communication, reflecting the worldview of English speakers.